2011
DOI: 10.1016/j.ejca.2011.04.035
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic hysterectomy is preferred over laparotomy in early endometrial cancer patients, however not cost effective in the very obese

Abstract: In general, TLH should be recommended as the standard surgical procedure in early stage endometrial cancer, also in patients>70 years of age. In obese patients with a BMI>35 kg/m2 TLH is not cost effective because of the high conversion rate. A careful consideration of laparoscopic treatment is needed for this subgroup. Surgeon experience level may influence this choice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 24 publications
(30 reference statements)
3
30
2
Order By: Relevance
“…Further analysis of trial data found TLH cost-effective for patients >70 years of age, but not for very obese patients with body mass index > 35. 18 In another clinical trial of hysterectomy for benign diagnoses, Garry et al 19 not only reported higher complication rates for LH but also confirmed a shorter hospital stay and faster postoperative recovery compared to TAH. Sculpher et al 20 found higher costs of laparoscopic hysterectomy compared to abdominal hysterectomy (£186) with similar QALYs resulting in incremental costs of £26 571 for each QALY gained.…”
Section: Discussionmentioning
confidence: 92%
“…Further analysis of trial data found TLH cost-effective for patients >70 years of age, but not for very obese patients with body mass index > 35. 18 In another clinical trial of hysterectomy for benign diagnoses, Garry et al 19 not only reported higher complication rates for LH but also confirmed a shorter hospital stay and faster postoperative recovery compared to TAH. Sculpher et al 20 found higher costs of laparoscopic hysterectomy compared to abdominal hysterectomy (£186) with similar QALYs resulting in incremental costs of £26 571 for each QALY gained.…”
Section: Discussionmentioning
confidence: 92%
“…Many authors concluded that it is not effective to perform laparoscopic hysterectomy in high-body mass index (BMI) women [3134]. Bijen et al noted that the risk of conversion from laparoscopy to laparotomy increases with BMI, with a rapid rise in women with a BMI >35 [31].…”
Section: Surgical Approach With Eec (Stage I Figo2009)mentioning
confidence: 99%
“…Bijen et al noted that the risk of conversion from laparoscopy to laparotomy increases with BMI, with a rapid rise in women with a BMI >35 [31]. …”
Section: Surgical Approach With Eec (Stage I Figo2009)mentioning
confidence: 99%
“…Obesity has been associated with a worse prognosis of endometrial carcinoma in several published studies, although there was no association in other and in Korean population studies (10)(11)(12)(13)(14). Obesity was once a contraindication for advanced laparoscopic procedures (15,16), although this has recently been reconsidered (17). Improved instrumentation and techniques have allowed the safe use of many advanced laparoscopic procedures in women with a high BMI (18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%